Circulating Adhesion Molecules VCAM-1, ICAM-1, and E-selectin in Carotid Atherosclerosis and Incident Coronary Heart Disease Cases: The Atherosclerosis Risk In Communities (ARIC) Study - Hwang, Shih-Jen; Ballantyne, Christie M.; Sharrett, A. Richey; Smith, Louis C.; Davis, Clarence E.; Gotto, Antonio M.; Boerwinkle, Eric (Circulation (New York, N.Y.), 1997)
Background Recruitment of circulating leukocytes at sites of atherosclerosis is mediated through a family of adhesion molecules. The function of circulating forms of these adhesion molecules remains unknown, but their levels may serve as molecular markers of subclinical coronary heart disease (CHD). Methods and Results To determine the ability of circulating vascular cell adhesion molecule-1 (VCAM-1), endothelial-leukocyte adhesion molecule-1 (E-selectin), and intercellular adhesion molecule-1 (ICAM-1) to serve as molecular markers of atherosclerosis and predictors of incident CHD, we studied 204 patients with incident CHD, 272 patients with carotid artery atherosclerosis (CAA), and 316 control subjects from the large, biracial Atherosclerosis Risk In Communities (ARIC) study. Levels of VCAM-1 were not significantly different among the patients with incident CHD, those with CAA, and control subjects. Higher levels of E-selectin and ICAM-1 were observed for the patients with CHD (means [ng/mL]: E-selectin, 38.4; ICAM-1, 288.7) and those with CAA (E-selectin, 41.5; ICAM-1, 283.6) compared with the control subjects (E-selectin, 32.8; ICAM-1, 244.2), but the distributions were not notably different between the patients with CHD and CAA. Results of logistic regression analyses indicated that the relationship of ICAM-1 and E-selectin with CHD and CAA was independent of other known CHD risk factors and was most pronounced in the highest quartile. The odds of CHD and CAA were 5.53 (95% CI, 2.51–12.21) and 2.64 (95% CI, 1.40–5.01), respectively, for those with levels of ICAM-1 in the highest quartile compared with those in the lowest quartile. Odds of CAA were 2.03 (95% CI, 1.14–3.62) for those with levels of E-selectin in the highest quartile compared with those in the lowest quartile. Conclusions These data indicate that plasma levels of ICAM-1 and E-selectin may serve as molecular markers for atherosclerosis and the development of CHD.